Deciding Who Works Where: An Analysis of the Distribution of Work within Native and Immigrant Families in Australia - Basilio, L (My University, 2009)
The paper examines whether there is an asymmetry in the distribution of market work and domestic work within families in Australia, and to what extent differences in earnings capacities of spouses can account for the division of labor. Using a Blinder-Oaxaca Tobit-type decomposition, we find that the difference in earnings capacities of Australian couples could explain about 30 and 20 percent of the observed disparities in spousal time allocation in market and domestic work, respectively. Most of the work gaps, however, appear to be accounted for by the differences in labor supply behaviors of partners rather than by the differences in earnings capacities.We further observe that the differences in wages are more relevant for immigrant families originating from non-English speaking countries.Convergence of gender wages would produce the greatest reduction in spousal specialization for this particular group.Given that immigrant women from non-English speaking background have high levels of formal qualifications, our results could assert the significance of improving the returns to human capital attributes of these immigrant women in reducing the imbalance in spousal work distribution.
Ruhr Economic Papers
Keywords: Culture; Employment; Culture -- Immigrants; Migration and settlement; Labour market; Culture; Employment; Immigrants; Migration and settlement; Employment and unemployment